Cobalt-catalyzed CH activation/CO formation: Synthesis of benzofuranones. Issue 3 (16th January 2020) - Hajipour, Abdol R.; Khorsandi, Zahra
Graphical abstract: Highlights: Palladium and oxidant-free CH activation reaction. Benzofuranones synthesis in moderate to excellent yields. Appling of cobalt catalytic system in direct lactonization reaction. The reactions were performed at room temperature, air conditions. Abstract: Herein, CH activation/CO formation reaction using novel cobalt catalytic system is reported. This reaction was given benzofuranones in moderate to excellent yields at room-temperature under air reaction conditions. The introduced strategy is efficient and low-cost method to synthesized benzofuranones from α, α-disubstitution acetic acid.